Luto manicomial e memórias colonizadas: lembranças de trabalhadoras de hospitais psiquiátricos - Mazetto, Tamiris Cristina Gomes (Universidade Federal de São Carlos, 2024)
This thesis aims to analyze memories about mental hospitals in the region of Sorocaba, state of São Paulo, through oral histories of women who worked in those places. Its objective is to investigate working conditions in asylums and the institutionalization of workers, considering the plots that articulate coloniality and asylum, especially in their intersections with issues of race and gender. The collective memory about asylums revealed that more than two thirds of the institutionalized people were black, the majority were illiterate, and came, in many cases, from other cities of the São Paulo state and other Brazilian regions. The hospitalized people found their self in a brutal chronic condition; Those called as “chronic” were subjected to the most violent “treatments”, they constituted the group most subject to asylum death, which included children and adolescents. Institutionalized women, the majority of whom were black, were also subjected to the violence of rape. Regarding work experiences, the exploitation of the work of female employees was noted, particularly under the discourse of “work for love”, as a mark of the historical abuse of reproductive work essentialized as feminine. The interviewees' memories were considered “emblematic memories”, considering the publicization of individual memories as an important force in the production of social ruptures. The division of the world and the fragmentation of biographies as traces of colonialism, with the perpetuation of racist, classist and misogynistic segregation, had repercussions on population cuts and on the “treatment” given to madness and the “crazy”, which possibly, raised boundaries in the workers’ own bodies: “border-bodies” between “work for love” and the operation of institutional violence. In the analysis about the permanence of denying and defensive contents in the processes of working and elaborating memories, inspired by Grada Kilomba's reflections on “colonial mourning”, this study proposed the concept of “asylum mourning”. This corresponds to the perpetuation of a siege on the social imaginary, through the repetition of the narrative that attributed to hospitalization in “psychiatry” the seal of the only possible action for the supposed support of people in intense psychosocial suffering, in a timeless way, for the benefit of maintaining of the powers, privileges and prestige of the “lord-owners” of the madness market. “Asylum mourning” produces the impediment of one’s own mourning and colonizes memories, senses and affections, enabling reflections on the difficulties in advancing anti-asylum psychiatric reform in Brazil.
Asylum mourning and colonized memories: memories of psychiatric hospital female workers
Keywords: Hospitais Psiquiátricos; Interseccionalidade; Colonialidade; Memória Coletiva; Psychiatric Hospitals; Intersectionality; Coloniality; Collective Memory; CIENCIAS HUMANAS::PSICOLOGIA; CIENCIAS HUMANAS; CIENCIAS DA SAUDE::MEDICINA::PSIQUIATRIA; OUTROS::ESTUDOS SOCIAIS; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA SOCIAL::PAPEIS E ESTRUTURAS SOCIAIS; INDIVIDUO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA DO TRABALHO E ORGANIZACIONAL; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA DA SAUDE